Pengembangan Model Bimbingan Kelompok Berbasis Islami untuk Meningkatkan Kecerdasan Emosional Siswa - Ningsih Fadhilah (LPPM UIN K.H. Abdurrahman Wahid Pekalongan, 2017)
This article examines the model of group guidance development that is effective in improving the emotional intelligence of senior high school students. This research used educational research and development method. The sample was chosen by purposive sampling to one group of 10 students. The result of this research is Islamic-based group guidance model. The Islamic group-based guidance model developed is a process of providing assistance by counselors to individual through a group atmosphere based on Islamic values in al-qur'an and hadith, enabling each member to learn to participate actively by utilizing the thought and experience of group members. The result of model implementation shows that the guidance of Islamic-based group proved effective in improving students' emotional intelligence. This increase occurs in all aspects of emotional intelligence. Wilcoxon statistical test result shows probability value below 0.05 (0.0025 <0.05), means that the guidance of Islamic-based group effective to improve students' emotional intelligence.